Characterisation of carotenoid and total retinol equivalent content in Ulam and medicinal species as alternative food intervention to combat vitamin A deficiency - Othman, Rashidi; Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian (Lifescience Global, 2017)
Vitamin A deficiency (VAD) is one of the continuous leading causes of children and pregnant women death. To overcome this malnutrition which currently affected one-third of the world population, there is always renewed interest in exploring numerous dietary sources rich in carotenoids which some of them serve as pre-cursors to vitamin A (pro- vitamin A). It is important that affordable staple foods be as nutritious as possible because poverty limits food access for much of the developing world’s population. Therefore, this study was aimed to explore various dietary sources for carotenoids in 28 ulam and medicinal species which are commonly consumed by the local folks. Carotenoid extraction using organic solvents was performed and analysis employed in this study through High Performance Liquid Chromatography revealed seven types of carotenoids in the food matrices; neoxanthin, violaxanthin, lutein, zeaxanthin, β-cryptoxanthin, α-carotene and β-carotene. Interestingly, these carotenoids profiles were found in varying concentration and composition in different species as well as in different period or season. Total carotenoids content quantified in all of the samples lies between 1.315 ± 0.007 to 190.301 ± 3.427 μg/g DW where cekur manis has the highest content. The total vitamin A activity (in terms of retinol equivalent, RE) of every species is also included in this study. The results suggested that at least 20 of the ulam and medicinal species may be used as alternative food intervention to eliminate VAD as a public health concern.